Factors Contributing to School Refusal among School Children - Mahmood, Iram; Inam, Attiya; Abiodullah, Muhammad (Nurture, 2015)
School refusal is critical problem for students’ academic success. For some students, going to school is their biggest fear, which has become a growing concern over the years, not only for parents, but school personnel as well. The present study was aimed to find out the prevalence and causes of school refusal among school children. 120 students of grade 7 and 8 and their parents were taken as sample from the Sadiq Memorial and District Public School, Kasur through simple random sampling. School refusal assessment scale revised (SRAS-R) was used to evaluate the functional conditions of school refusal. Data was analyzed through frequency, percentage tables, analysis of variance (ANOVA) and independent sample t- test. The results indicated that boys experienced more refusal than boys. Major cause of school refusal was found to be more due to pursue attention from significant others. It is recommended that further research should be conducted to see the factors contributing to school refusal among school children.